On Turkey's Trail as a Rising Middle Power in the Network of Global Governance: Preferences, Capabilities, and Strategies - (:unkn) unknown (My University, 2014)
0

Acknowledging Turkey as a rising/emerging middle power , occupying a middle ground between traditional (or Western) middle powers and non-traditional middle powers, this paper aims to reassess Turkey s changing power and position in the complex power hierarchies and the changing architecture of global governance through its preferences, capabilities and strategies by using a comparative analysis. It then briefly resumes its findings to assess the driving factors, conditions and specific characteristics explaining Turkey s contribution to global governance compared to a cluster of eight selected countries composed of the five BRICS countries, labeled as non-traditional middle powers, and Canada, Australia and South Korea, as traditional middle powers. Finally, it looks at Turkey s contribution to global governance at the institutional level, with a special focus on Turkey s 2015 G20 presidency as a test case for understanding its global governance activism. In the final analysis, this study underlines that Turkey s ambitious agenda for its G20 presidency gives clear signals of its future preferences and middle power activism in less hierarchical G20-type forums in which developed and developing countries are equally represented and middle power countries are allowed more manoeuvring capacity.
Keywords: Uluslararası İlişkiler